Teknik Relaksasi Progresive Untuk Menurunkan Tingkat Kecemasan Siswa Menghadapi Ujian Nasional Berbasis Komputer - Nurnaningsih nurnaningsih (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
This study aims to apply Relaxation Techniques to reduce the level of anxiety of high school students when they face the Computer-Based National Examination (UNBK). Participants in this study were students of class XII who received the highest score on the anxiety scale, meaning students with high and moderate anxiety levels. The instrument used was the DASS (Depression Anxiety Stress Scale) anxiety scale consisting of 42 statement items. The results of the preliminary study showed 60% of students experienced high levels of anxiety, and 30% were moderate and 10% experienced low levels of anxiety. Treatment performed on students is by using Progressive Relaxation Techniques for 6 sessions. Every 2x session an evaluation of the level of anxiety is completed. Students who are categorized as experiencing severe levels of anxiety and are being treated using this progressive relaxation method, they are given the task to do also relaxation at home every day before going to sleep and wake up. The results of the study after 6 progressive relaxation sessions, it was found that the level of anxiety of the students was reduced ie students who experienced severe anxiety levels were reduced to as much as 20%, who experienced moderate levels of anxiety to be completely gone. An effective Progressive Relaxation Technique is used to reduce the level of anxiety of students who will face the National Examination